DETERMINAN KUALITAS HASIL PEMERIKSAAN (Studi Empiris Pada BPKP Perwakilan Provinsi Jawa Tengah) - Evi Tiara Dewi, 13.05.52.0081; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2017)
The purpose of this research is to examine the effect of due professional care, objectivity, independency, act upon code of ethics, accountability, proficiency, and job experience on the quality of audit result at Representatives BPKP of Central Java. The population of this study is civil servants whose work at Representatives BPKP of Central Java. The sampling technique using random samplingand sampling sufficiency with slovin formula. Based on calculations obtained by a sample of 70 respondents. Data analysis was performed with multiple linear regression model. The result showed that objectivity, act upon code of ethics and proficiency have a significant effect on quality of audit result. While the due professional care, independency, accountability, and job experience have no significant effect on quality of audit result.Keywords: Due Professional Care, Objectivity, Independency, Act upon Code of Ethics, Accountability, Proficiency, Job Experience, Quality of Audit Result